Environmental preservation: Mrican youth innovation on slummed irrigation channels (Bendung Lepen Gajah Wong) - Ulfah, Tsaqifa Taqiyya; Kamala, Izzatin; Latifah, Shinta Noor (Journal of Community Service and Empowerment, 2020)
The environment is something that is very influential in life, but cannot be avoided from the term pollution. The problem is a top priority for local residents, so the tips needed are environmental preservation to maintain a beautiful environment and the balance of the ecosystem. The purpose of this study is to describe the origin of the formation Bendung Lepen Gajah Wong, the role of youth in the construction of Bendung Lepen Gajah Wong, and the function of Bendung Lepen Gajah Wong in the lives of local residents. The qualitative method is appropriately used in this program by conducting interviews, observations, and documentation to obtain relevant data or information. The results of this program indicate that 1) before Bendung Lepen Gajah Wong was built, it was a river that was used for irrigation channels which was filled with waste and garbage so as to pollute the environment. 2) Seeing the condition of the environment which is filled with garbage, there arises the awareness of the young people around to preserve the environment by cleaning up trash around the river and Bendung Lepen Gajah Wong. 3) Bendung Lepen Gajah Wong weir currently functions as an irrigation channel in irrigating rice fields, as a tourist attraction as well as an educational facility for visitors, especially for children, and as a counterweight to the ecosystem.